Herbal Medicines and Pediatric Diseases - S Saeidnia; Z Dasian; A Hadjiakhoondi (Institue of Medicinal Plants, ACECR, 2010)
Although, medicinal Plants and herbal remedies have an important usage in the treatment of several diseases, the potential herbal contributions to pediatric medicine is receiving much attention based on WHO definitions. Children have special needs and nature abounds in special plants that address these needs. The herbalist will always select remedies that have a tonic action as the core of herbal prescriptions for children. The healing capacity of children can be quite incredible and often all that is needed is a gentle herbal helping hand, rather than the stronger effects necessitate for adults. It is important to find the right balance between the appropriate use of drugs and herbs. There are times when antibiotics or surgery can be life saving. Similarly there are times when using the powerful tools of modern medicine is excessive and the desired results can be achieved using herbal medicine.